Teaching the Arabic Language between the Challenges of Globalization and the Enhancement of National Identity - Alsaied, Mohamad Abdullah (Journal of Ecohumanism, 2024)
The focus of this research is to examine the duality of language and identity within contemporary Arab culture, particularly in terms of their civilizational interrelation and their influence by emerging social and cultural phenomena. This analysis is situated within a global context where cultural boundaries between societies have become increasingly blurred. Although the history of the Arabic language demonstrates its effective dialogue with surrounding elements and its capacity to assimilate various scientific and intellectual activities over an extended period, including the Abbasid and Andalusian eras, observations indicate that contemporary Arabic is no longer capable of meeting the cognitive needs of its speakers. This is especially evident in its diminished role in scientific advancement and its reduced prevalence in everyday speech. Numerous indicators highlight this trend, such as the declining presence of Arabic in academic research, the widespread use of colloquial dialects, and their strong competition with Modern Standard ArabLanguageic (Fusha) in fields like art and education. Considering that the Arabic language, like other languages, serves as a vessel for elements of Arab identity, there is no doubt that the decline of its presence in the domains of communication and scientific research has a direct impact on the formation of that identity. This situation urgently calls for careful management of our relationship with our language. In this regard, what we observe is the necessity to enhance the presence of Arabic in our daily and scientific lives. This is achievable by diversifying Arabic teaching methodologies for both native and non-native speakers to ensure that it keeps pace with all current and future scientific developments.